In Situ Diffraction Study of the High‐Temperature Decomposition of t′‐Zirconia. Issue 1 (26th September 2014) - Krogstad, Jessica A.; Gao, Yan; Bai, Jianming; Wang, Jun; Lipkin, Don M.; Levi, Carlos G.; Sampath, S.
<x xml:space="preserve">Abstract</x> The mechanisms of phase destabilization upon aging of the metastable t′ phase of yttria‐stabilized zirconia (YSZ) are poorly understood, despite its broad application in thermal barrier coatings. To provide insight, synchrotron X‐ray diffraction (XRD) with a quadrupole lamp furnace is used to examine the temperature response, including thermal expansion and phase evolution, of a 9 mol% (8 wt%) YO1.5t′‐8YSZ. The thermal expansion of equilibrated YSZ powders ranging from 0 to 18.4 mol% YO1.5 is also investigated to better understand the effect of composition on the thermal expansion anisotropy. The T0(c/t) temperature for t′‐8YSZ is estimated to be 1640°C. Full decomposition of the t′ phase into a coherent mixture of a Y‐lean tetragonal phase (t) and a Y‐rich cubic phase (c) that coarsen over time is observed at elevated temperatures; however, upon quenching, the t′ phase reappears in the diffraction profile. This supports our evolving understanding that the t′ phase observed by XRD in aged samples is a microstructural artifact due to the coherency strain between the t and c phases.